Piloting PrePex for Adult and Adolescent Male Circumcision in South Africa – Pain Is an Issue - Lebina, Limakatso (PLoS One, 2015)
BACKGROUND: The World Health Organisation and the Joint United Nations Programme on HIV/AIDS have recommended the scale-up of Medical Male Circumcision (MMC) in countries with high HIV and low MMC prevalence. PrePex device circumcision is proposed as an alternate method for scaling up MMC. OBJECTIVE: Evaluate safety and feasibility of PrePex in South Africa. DESIGN: A multisite prospective cohort PrePex study in adults and adolescents at three MMC clinics. Participants were followed-up 8 times, up to 56 days after PrePex placement. RESULTS: In total, 398 PrePex circumcisions were performed (315 adults and 83 adolescents) their median ages were 26 (IQR: 22–30) and 16 years (IQR: 15–17), respectively. The median time for device placement across both groups was 6 minutes (IQR: 5–9) with the leading PrePex sizes being B (30%) and C (35%) for adults (18–45 years), and A (31%) and B (38%) for adolescents (14–17 years). Additional sizes (size 12–20) were rarely used, even in the younger age group. Pain of device application was minimal but that of removal was severe. However, described pain abated rapidly and almost no pain was reported 1 hour after removal. The Adverse Events rate were experienced by 2.7% (11/398) of all participants, three of which were serious (2 displacements and 1 self-removal requiring prompt surgery). None of the Adverse Events required hospitalization. The majority of participants returned to work within a day of device placement. CONCLUSION: Our study shows that PrePex is a safe MMC method, for males 14 years and above. PrePex circumcision had a similar adverse event rate to that reported for surgical MMC, but device removal caused high levels of pain, which subsided rapidly.